2023
DOI: 10.3390/nano13162302
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an Amethyst-like MoS2@Ni9S8/Co3S4 Rod Electrocatalyst for Overall Water Splitting

Abstract: Transition metal sulphide electrocatalytic materials possess the bright overall water-splitting performance of practical electrocatalytic technologies. In this study, an amethyst-like MoS2@Ni9S8/Co3S4 rod electrocatalyst was constructed via a one-step hydrothermal method with in-situ-grown ZIF-67 nanoparticles on nickel foam (NF) as a precursor. The rational design and synthesis of MoS2@Ni9S8/Co3S4 endow the catalyst with neat nanorods morphology and high conductivity. The MoS2@Ni9S8/Co3S4/NF with the amethyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…9H5E-CF 9H5E-CC showed high stability with negligible voltage change. Additionally, compared with the reported bifunctional catalysts for HER, OER, and overall water splitting in alkaline electrolytes, a competitive overpotential of 142 mV (η 10 ) for HER, 294 mV (η 50 ) for OER, and 1.88 V (at 50 mA cm −2 ) for overall water splitting were achieved for the MoO 3 -NiS x catalyst, as shown in Table S4 [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9H5E-CF 9H5E-CC showed high stability with negligible voltage change. Additionally, compared with the reported bifunctional catalysts for HER, OER, and overall water splitting in alkaline electrolytes, a competitive overpotential of 142 mV (η 10 ) for HER, 294 mV (η 50 ) for OER, and 1.88 V (at 50 mA cm −2 ) for overall water splitting were achieved for the MoO 3 -NiS x catalyst, as shown in Table S4 [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/catal13111426/s1, Figure S1 S1: Listing of the experimental parameters for fabricating the samples; Table S2: R s and R ct values of 9H5E-CC, 9H-CC, and 9H15-CC; Table S3: R s and R ct values of 9H5E-CF, 9H-CF, and 9H15-CF; Table S4: Comparison of the water splitting performance of the catalyst in this study with that of other reported bifunctional catalysts in 1 M KOH. References [39][40][41][42][43][44][45][46][47][48][49][50][51] are cited in the Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%